MOTHER’S HEALTH LITERACY WITH STUNTING INCIDENCE OF TODDLERS IN JEMBER - Mazida, Zulfa; Noveyani, Adistha Eka; Prasetyowati, Irma (The Indonesian Journal of Public Health, 2024)
Introduction: Mothers have a role in caring for and fulfilling toddler nutrition which is very important to prevent stunting in toddlers. Mothers’ skills in carrying out their roles are influenced by mothers’  knowledge through health literacy, namely the capability to access, assess, and process health information. Prevalence of stunting in East Java was 26.8% in 2019, exceeding the limit set by WHO. Jember is the second area contributing to the largest prevalence of stunting in East Java. Aims: This study aimed to analyze the relationship of mothers’ health literacy with stunting incidence of toddlers. Methods: This study used a case control design. The respondents were mothers with stunting toddlers (n=51) and mothers with non-stunted toddlers (n=51). The secondary data sources were the stunting data of the Kalisat Primary Healthcare in February 2022 and the primary data sources were the results of interviews used the HLS-EU-16 Indonesia Questionnaire. Data analysis used chi-square test. Results: There was a relationship between mothers’ health literacy and  stunting incidence of toddlers with a p-value of  0.001 (p-value < 0.05 so that the two variables have a significant relationship. Conclusion: Mothers’ health literacy has a strong association with stunting incidence of toddlers.